Deer wars : science, tradition, and the battle over managing whitetails in Pennsylvania - Frye, Bob, 1967- (Pennsylvania State University Press, 2006)
The story of deer management in Pennsylvania is as complex as it is controversial. From the disappearance of deer in Pennsylvania forests at the beginning of the twentieth century to the population explosion that occurred in the latter half of the century, the balance between herd size and a healthy forest has long been a difficult one. In Deer Wars, Bob Frye examines this controversy and the effect that herd management has had on all of the citizens of Pennsylvania: farmers managing deer invasions and property rights, hunters dealing with changing herd densities and ever-complex restrictions, state agencies juggling the rights of hunters with the needs of commercial interests, all with stakes in the success and health of the deer herd. Now with deer harvests decreasing, Chronic Wasting Disease becoming a potential threat, and forests showing serious signs of trouble, the need for compromise from all of the players is essential, but is it possible? This well-researched and engrossing book explores that question.